Biomechanical parameters of running technique of sprint athletes-finalists of world championship - Balandin, S.; Balandina, I.; Zayko, D.; Dmitriev, I. (Theory and Practice of Physical Culture, 2022)
Objective of the study: to compare the spatio-temporal, kinematic and angular characteristics of the distance running technique of the strongest 100 and 200 m sprinters in the world.Methodology of the study. The study analyzed the data of the spatio-temporal, kinematic and angular characteristics of distance running presented in the IAAF biomechanical report of the men's 100m and 200m finals of the 2017 World Ath-letics Championships.Results of the study. In the middle of a straight line in a 100 m run, the average speed is 11,60±0,06 m/s, in a 200 m run - 10,31±0,09 m/s. The difference in speed is achieved due to the step rate (4,80±0,08 stride/s and 4,27±0,05 stride/s, respectively, p=0,05), because the stride length at both distances is identical and is equal on average to 2,42 m (Table 1). A high step rate per 100 m is achieved due to the shorter time of the contact time (0,093±0,002 s and 0,103±0,002 s, p=0,05) and flight time (0,116 ±0,002 s and 0,132±0,003 s, p=0,05). When placing the leg on a support, reliably significant differ-ences (p=0,05) are observed in the angle of inclination of the body, the angle between the thigh of the swinging leg and the vertical line. When removing the leg from the support, a reliably significant difference (p=0,05) is observed in the angle of inclination of the body and the angle between the lower leg of the supporting leg and the horizontal line.